Digital Marketing Strategies to Increase Sales of Teh Poci Products Using Instagram: A Systematic Literature Review (SLR) Method - Ariska Ambar Wati; Meisy Andriani Harahap (PT. Hidayat Muda Intelektual, 2025)
The increasing number of Instagram users each year indicates that the platform has strong potential for continued growth and relevance in the realm of visual content sharing and social interaction in the future. Instagram has proven to be an effective marketing medium for boosting the sales of Es Teh Poci products, as it offers opportunities to reach a broad audience, build an attractive brand image, foster customer relationships, and encourage purchases. The objective of this study is to identify effective digital marketing strategies to increase the sales of Es Teh Poci products through the Instagram application. This research employs a qualitative method using a literature review approach. The data utilized in this study are secondary data obtained from relevant research journals and other credible sources. The findings indicate several strategies to enhance marketing performance on Instagram, including utilizing the comment section and direct messages for direct and personalized promotions, offering incentives to consumers, leveraging influencers, increasing content aligned with social media challenges and trends, reposting user-generated content as testimonials, and incorporating interactive content in both feeds and stories to engage with the audience and evoke emotional responses that may lead to purchase decisions. To further boost sales of Teh Poci products via Instagram, it is essential to focus on compelling content strategies, effective promotional efforts, and active audience engagement